Pengaruh Duta Merek Tiara Andini terhadap Pembelian Impulsif melalui Kepercayaan Merek pada Produk Garnier - Zulfikar, Rizki; Sahrul Aditya Rahman (Fakultas Ekonomi dan Bisnis Universitas Komputer Indonesia, 2025)
This research investigates how brand ambassadors influence impulse buying behavior by way of brand trust among Garnier consumers on TikTok Shop. As a rapidly expanding social commerce platform, TikTok Shop has distinctive features—such as real-time engagement and algorithm-driven content personalization—that encourage spontaneous purchasing decisions. The study employs a quantitative approach using a descriptive-verificative research design. Primary data were gathered from 100 respondents who had previously purchased Garnier products via TikTok Shop, while secondary data were sourced from relevant academic publications. Data analysis was conducted using SEM-PLS to examine both direct and mediating effects among the research variables. The findings reveal that brand ambassadors have a significant effect on brand trust but do not exert a direct influence on impulse buying. Conversely, brand trust significantly affects impulse buying behavior and serves as a mediating variable in the relationship between brand ambassadors and impulsive purchasing. The originality of this study is reflected in its emphasis on the TikTok Shop environment and the involvement of digital-native brand ambassadors in shaping consumers’ impulsive buying tendencies